2019
DOI: 10.21608/ejh.2019.10575.1100
|View full text |Cite
|
Sign up to set email alerts
|

The possible therapeutic effect of rebamipide and stem cell derivative microvesicles on experimentally provoked colitis in rats: Histological and immuno hisochemical study.

Abstract: Background Ulcerative colitis (UC) is a chronic inflammatory disorder. Clinically, there are periods of pain in abdomen and bloody diarrhea. The used medication induce clinical diminution, but with many difficulties. Aim of the study Evaluation the beneficial outcomes of rebamipide and microvesicles come from mesenchymal stem cells on treatment of induced colitis. Material and methods Fifty adult male albino rats were divided into 5 groups. Group I was the control group. Group II rats received intra-colonic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…BMSCs have been used by several researchers in the treatment of experimental colitis using various animal models, including mice, rats, and Guinea pigs (Table 4). In these animals, some researchers have used trinitrobenzene sulfonic acid (TNBS) to induce colitis [37,[65][66][67][68], while several studies reported the use of dextran sulfate sodium (DSS) to induce colitis models [47,48,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] and many authors applied acetic acid to induce colitis [1,3,4] (Table 4). The first BMSCs transplantation was conducted in 2006 in a TNBS-induced colitis mice model, revealing the important role of cell therapy in the repair of injured intestinal mucosa, as well as the downregulation of immune function of T cells [65].…”
Section: In Vivo Studies Using Bmscs In the Treatment Of Ucmentioning
confidence: 99%
See 1 more Smart Citation
“…BMSCs have been used by several researchers in the treatment of experimental colitis using various animal models, including mice, rats, and Guinea pigs (Table 4). In these animals, some researchers have used trinitrobenzene sulfonic acid (TNBS) to induce colitis [37,[65][66][67][68], while several studies reported the use of dextran sulfate sodium (DSS) to induce colitis models [47,48,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] and many authors applied acetic acid to induce colitis [1,3,4] (Table 4). The first BMSCs transplantation was conducted in 2006 in a TNBS-induced colitis mice model, revealing the important role of cell therapy in the repair of injured intestinal mucosa, as well as the downregulation of immune function of T cells [65].…”
Section: In Vivo Studies Using Bmscs In the Treatment Of Ucmentioning
confidence: 99%
“…The differentiation of BMSCs into colonic interstitial lineage cells could produce TGF-β1 and VEGF that could further participate in the healing of colitis lesions [69]. BMSCs in a DSS-induced colitis rat model were demonstrated to differentiate into several cells, to dampen the inflammation and to repair ulcerations and the distorted crypt architecture, and reduce the loss of surface columnar epithelium [70]. BMSC microvesicles, together with rebamipide in the DSS-induced colitis rat model, resulted in an improvement in the prompted colonic lesions [71].…”
Section: In Vivo Studies Using Bmscs In the Treatment Of Ucmentioning
confidence: 99%